Preparation and Characterization of Zno Nano particles Prepared by Hydrothermal Method - Mohammed Ajmi Abd; Khalid Hamdi Razeg; Raad M.S Al-haddad (Tikrit Journal of Pure Science)
In this study,the nanoparticles of zinc oxide were readily prepared  through Hydrothermal process by using zinc nitrate hexahydrate, and Sodium hydroxide as aprecursors. The surface topology, and crystalline structure of prepared ZnO nanoparticles were studied. X-ray diffraction (XRD) revealed that the prepared ZnO nano particles is highly crystalline, having (wurtzite) crystal structure.  The optical analysis by UV–vis showed that these ZnO nano particles have considerable blue shift in the optical band gap energy (Eg = 4.9eV), and this may be to the  quantum confinement effect of nano particles. The FT-IR results shows the  existence of OH, COO, H2O groups the characteristic vibrational modes of Zn–O were identified. and AFM analysis showed that the diameters of the ZnO particles is in ananometer range of (70-74)nm